Предмет: Математика,
автор: daria114
ПРОШУ О ПОМОЩИ,СРОЧНО!!!!!!!
Приложения:
![](https://files.topotvet.com/i/8d1/8d1c109c2c10290869add17044238909.png)
Ответы
Автор ответа:
0
8 - 2*(4 - 3х) = 8 - ( 8 - 6х ) = 6х
- х - ( - 4х) = - х + 4х = 3х
- ( у - х ) + ( х + у) = - у + х + х + у = 2х
- ( 4у - 3х) + 10*( 2/5у - 1/2х ) = - 4у + 3х + 4у - 5х = -2х
- 0,2у - 0,25х + 1/5у - 3/4х = -1/4х - 3/4х = - 1 (у уничтожаются)
- х - ( - 4х) = - х + 4х = 3х
- ( у - х ) + ( х + у) = - у + х + х + у = 2х
- ( 4у - 3х) + 10*( 2/5у - 1/2х ) = - 4у + 3х + 4у - 5х = -2х
- 0,2у - 0,25х + 1/5у - 3/4х = -1/4х - 3/4х = - 1 (у уничтожаются)
Похожие вопросы
Предмет: Геометрия,
автор: lizaggoludeva
Предмет: Математика,
автор: aigulmadanbekova2
Предмет: Химия,
автор: aleksandrakiskina0
Предмет: Биология,
автор: foggy765